Cobalt Hexacyanoferrate as Cathode Material for Na+ Secondary Battery - Takachi, Masamitsu; Matsuda, Tomoyuki; Moritomo, Yutaka (Applied physics express, 2013)
We investigated structural and electrochemical properties of thin film electrodes of cobalt hexacyanoferrate, Na x Co[Fe(CN) 6 ] 0.90 2.9H 2 O, against $x$. The compound exhibits a high capacity of 135 mAh/g and an average operating voltage of 3.6 V against Na, with a good cyclability. The discharge curve exhibits two plateaus at ${≈}3.8$ and ${≈}3.4$ V, which are ascribed to the reduction processes of Fe 3+ and Co 3+ , respectively. The ex situ X-ray diffraction (XRD) profiles reveal the robust nature of the host framework against Na + intercalation/deintercalation. Thus, cobalt hexacyanoferrate is a promising candidate for the cathode material of sodium-ion secondary battery (SIB).